Case report: An autopsy case of pilsicainide poisoning - Takei, Sella; Kinoshita, Hiroshi; Kumihashi, Mitsuru; Jamal, Mostofa; Abe, Hiroko; Kimura, Shoji (Frontiers in Pharmacology, 2023)
We present a fatal case of pilsicainide poisoning. Quantitative toxicological analysis revealed that the concentrations of pilsicainide in femoral blood and urine samples were 17.5 μg/mL and 136.9 μg/mL, respectively. No morphological changes due to poisoning were observed. Based on the autopsy findings, results of the toxicological examination, and investigation by the authorities, we concluded that the cause of death was due to pilsicainide poisoning.